Pengaruh Current Ratio, Debt Equty Ratio, dan Return On Assets terhadap Price Book Value pada Perusahaan Pertambangan Sub Sektor Batu Bara yang Terdaftar di Bursa Efek Indonesia Periode 2020-2022 - safutri, Rezi; Dunakhir, Samirah; Azis, Fajriani (VISA: Journal of Vision and Ideas, 2024)
This research aims: (1) To analyze the influence of Current ratio (CR), Debt to equity ratio (DER), and Return on Assets (ROA) simultaneously on Price Book Value (PBV) in coal companies listed on the IDX, ( 2) To analyze the Current ratio (CR), Debt to equity ratio (DER), and Return on Assets (ROA) partially on Price Book Value (PBV) in coal companies listed on the IDX, (3) To analyze which variables which has the most dominant influence on the Price Book Value (PBV) of coal companies listed on the IDX. The variables in this research are (1) Current Ratio, (2) Debt Equty Ratio, (3) Return On Assets, and (4) Price Book Value. The population of this research is all 42 coal companies listed on the Indonesia Stock Exchange. Meanwhile, the samples in the research: (1) Coal companies listed on the Indonesia Stock Exchange from 2020-2022, (2) Coal companies that published financial reports during the 2020-2022 period, (3) Manufacturing companies that have a positive company value of 2020-2022. Data collection is carried out using documentation. Data analysis was carried out using classical assumption tests, multiple linear regression analysis and hypothesis testing. The results of this research show that the Curret Ratio has a significant effect on Price book value with a sig value of 0.318, the Debt Equty Ratio has a significant effect on price book value with a sig value of 0.009, and Return On Assets has a significant effect on price book value with a sig value of 0.038 and has a significant effect on price book value. simultaneously with a sig value of 0.023.